2016
DOI: 10.1186/s13287-016-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by mesenchymal stem cells in treating human autoimmune disease-associated lung fibrosis

Abstract: BackgroundInterstitial pneumonia in connective tissue diseases (CTD-IP) featuring inflammation and fibrosis is a leading cause of death in CTD-IP patients. The related autoimmune lung injury and disturbed self-healing process make conventional anti-inflammatory drugs ineffective. Equipped with unique immunoregulatory and regenerative properties, mesenchymal stem cells (MSCs) may represent a promising therapeutic agent in CTD-IP. In this study, we aim to define the immunopathology involved in pulmonary exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…IL-6 is small-molecular glycopeptides secreted by activated T lymph cells. There are studies shows that IL-6 has close relations with fibrosis of pulmonary interstitium [16,17]. In this study, IL-6 level in serum of CTD-ILD and CTD patients higher than normal level obviously, IL-6 level of CTD-ILD patients higher than CTD patients (P<0.05).…”
Section: Discussionmentioning
confidence: 43%
“…IL-6 is small-molecular glycopeptides secreted by activated T lymph cells. There are studies shows that IL-6 has close relations with fibrosis of pulmonary interstitium [16,17]. In this study, IL-6 level in serum of CTD-ILD and CTD patients higher than normal level obviously, IL-6 level of CTD-ILD patients higher than CTD patients (P<0.05).…”
Section: Discussionmentioning
confidence: 43%
“…29 Although it is commonly believed that antifibrosis of CXCL10 correlates to inhibit fibroblast migration, the effect of CXCL10 on αsmooth muscle actin and IL-6 expression to prevent myofibroblast differentiation is also reported. 30 In our study, after nab-PTX treatment, cancer cells increase CXCL10 expression, and this CXCL10 might decrease CAF IL-6 expression and suppress CAF tumor-promoting ability when the nab-PTX pretreated cancer cell-cultured medium was used to stimulate CAF.…”
Section: Discussionmentioning
confidence: 56%
“…It is also known that MSCs could exert immunoregulatory effects through different mechanisms, including immune cell interaction, production of soluble factors, and Treg generation (Liu et al, ). We confirmed that preconditioning hUCB‐MSCs with IL‐1β and IFN‐γ accelerated the secretion of IL‐10 and increased the differentiation of Tregs.…”
Section: Discussionmentioning
confidence: 99%